Analysis on Ultrasonic TOFD Imaging Testing for Ultra-thick-walled EBW Joint of Aluminum Alloy. (2017) - Cong, S.; Zhang, W.W.; Zhang, J.Y.; Gang, T.
Abstract: In order to complete the defect inspection and welding performance evaluation of the ultra-thick-walled aluminum alloy welded joint by electron beam welding (EBW), the ultrasonic time of flight diffraction (TOFD) D-scan imaging inspection investigations were carried out for the welded joint with the thickness of 165mm. Aiming at accurately identifying the defect information in the whole thickness area of the weld joint, a multiple scanning method combined with the double surface inspection with different separations of transducers and different refraction angle of acoustic beam was proposed to make the main beam of the transmitted and received transducers cover the whole weld zone. The experiments with different inspection parameters were performed by the top and bottom surface scanning for the four artificial side-drilled holes (SDHs) in different depth. The testing results of A-surface and B-surface scanning with the separation of 160mm and the refracted angle of 45° show that the defects in the depth more than 20mm can be accurately sized and positioned, while that in the depth less than 20mm at the vicinity of top surface are in the inspection blind zone. However, the defect diffracted waves are distinguished from the lateral waves obviously in the A-surface scanning with the separation of 72mm and the refracted angle of 68°. Large numbers of welding defects in the middle depth area and two sides of the weld zone can be observed by D-scan image. It is shown that the novel scanning method can effectively improve the inspection difficulties of ultra-thick-wall aluminum alloy weld and its inspection blind zone.